1969
DOI: 10.1017/s0021932000007355
|View full text |Cite
|
Sign up to set email alerts
|

Multiple births in Australia, 1944–63

Abstract: From statistics on Australian confinements during the period 1944-63 it seems that the following conclusions can legitimately be drawn:(1) The proportion of multiple births increases with increasing age of mother up to about age 37, turns, and decreases thereafter.(2) The proportion of multiple births increases with increasing age of father up to about age 34-38 and is fairly constant thereafter.(3) The variation with age of father, however, only arises because of the high correlation with age of mother which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Birth order for each twin birth correlates well with the Australian study (Pollard, 1969), with multiple birth occurrence decreasing after the first year of marriage (first birth), which possibly indicates that twin births occur more often when the first child is born to a women over 30. Figure 5 shows the number of infants and twins born in the study villages over the period 1870-1940.…”
Section: Mother's Age and Birth Ordersupporting
confidence: 60%
See 1 more Smart Citation
“…Birth order for each twin birth correlates well with the Australian study (Pollard, 1969), with multiple birth occurrence decreasing after the first year of marriage (first birth), which possibly indicates that twin births occur more often when the first child is born to a women over 30. Figure 5 shows the number of infants and twins born in the study villages over the period 1870-1940.…”
Section: Mother's Age and Birth Ordersupporting
confidence: 60%
“…Using statistics on Australian births during the period 1944-63, Pollard (1969) concluded that the proportion of multiple births increases with increasing mother's age until 37, and decreases thereafter, and that the proportion of multiple births decreases after the first year of marriage.…”
Section: Factors Affecting Twin Birthsmentioning
confidence: 99%
“…We do not know the causes of these changes in DZ twinning rates, nor do we know much in general about the determinants of DZ twinning, except that age and ethnicity play a role (Nylander, 1983). DZ twinning has been viewed as a marker of both reproductive failures and high fecundity (Bulmer, 1959;Eriksson & Fellman, 1967;Nylander, 1975;Pollard, 1969) and the decline in DZ twinning has been interpreted as a sign of declining fecundity. Monozygotic (MZ) twinning rates tend to remain constant over time.…”
mentioning
confidence: 99%
“…Among the sorts of evidence he considered were the prompt postmarital conceptions [4,9] and prompt postwar conceptions [3,8] of DZ twins. He found that within the reproductive histories of women bearing DZ twins, the conception delays leading to first-born DZ twin pairs were less than those leading to first-born singletons.…”
mentioning
confidence: 99%